The Mind thinking - Bull, Peter; Hutton, Richard; Jackson, Lisa. (New York WNET, 1988)
Delving into the root and background of the mind, this episode explores the extraordinary network that comprises human thought. The frontal lobe and pre-frontal cortex are zeroed in on as the key staging areas for integration in the brain; the place where memory, emotion and intelligence come together to produce conscious activity.
VHS
Narrator, George Page.
Keywords: Neurophysiology; Thought and thinking; Psychology